Prevalence and predictors of depressive and anxiety symptoms among medical students in a public university in Malaysia - Saddique, Ayesha (2022)
Introduction: Depression and anxiety are the commonest global mental issues, associated with health challenges among medical students. The nature of education in medicine is demanding, with many medical students influenced by different factors linked with depressive and anxiety symptoms during their studies. Objective: This study is aimed at determining the prevalence and predictors of depressive and anxiety symptoms among medical students at Universiti Putra Malaysia (UPM). Methodology: This correlational study involved 256 medical students ranging from first to the fifth year at the Faculty of Medicine and Health Sciences, UPM. A universal sampling technique was employed for data collection. The data were gathered by an online self-administered questionnaire consisting of demographic items, the Rosenberg Self-Esteem Scale, the Automatic Thought Questionnaire, the Emotional Regulation Questionnaire, the Multidimensional Scale of Perceived Social Support, the Generalized Anxiety Disorder-7 Scale, and the Patient Health Questionnaire-9 Scale. The data were analysed using the Statistical Package for the Social Sciences (SPSS) (version 26). Descriptive analysis was used to describe the socio-demographic characteristics of the participants. Bivariate analysis was carried out to examine the correlates of depressive and anxiety symptoms. As for multivariate analysis, hierarchical multiple regression analysis was carried out to examine the predictors of depressive and anxiety symptoms. Results: The prevalence of at least moderate depressive symptoms was 39.5%, and the prevalence of at least moderate anxiety symptoms was 53.9% among medical students. At the bivariate level, age [r = -.16 and p =.007], year of study [r = -.16, p = .010], self esteem [r = -.49, p = .000] were negatively correlated with depressive symptoms; age [r = -.20, p = .001], year of study [r = -.16, p = .010], self-esteem [r = -.36, p = .000], cognitive reappraisal [r = -.27, p = .000], social support from other [r = -.21, p = .001], social support from family [r = -.29, p = .000], and social support from friends [r = -.15, p = .016] were all negatively correlated with anxiety symptoms. On the other hand, automatic negative thoughts [r = .78, p = .000] were positively correlated with depressive symptoms; gender [r = .13, p = .036] and automatic negative thoughts [r = .68, p = .000] were positively correlated with anxiety symptoms. Nonetheless, marital status, monthly household income, living conditions, study hours per day, and expressive suppression were not significantly correlated with depressive and anxiety symptoms. Meanwhile, the predictors of depressive symptoms were gender (p = 0.000) and automatic negative thoughts (p = 0.000), and the predictors of anxiety symptoms were age (p = 0.028), years of study (p = 0.038), living conditions (p = 0.046), and automatic negative thoughts (p = 0.000). Conclusion: Findings from this study indicate a significant proportion of medical students at UPM had depressive and anxiety symptoms. Further findings from the study indicate that automatic negative thoughts were a significant predictor of both depressive and anxiety symptoms among UPM medical students. These automatic negative thoughts can be managed by cognitive behaviour therapy (CBT).